Smoked Marijuana as a Cause of Lung Injury - Tashkin, D.P. (Monaldi Archives for Chest Disease, 2005)
P. Tashkin. In many societies, marijuana is the second most commonly smoked substance after tobacco. While Î”9-tetrahydrocannabinol (THC) is unique to marijuana and nicotine to tobacco, the smoke of marijuana, like that of tobacco, consists of a toxic mixture of gases and particulates, many of which are known to be harmful to the lung. Although far fewer marijuana than tobacco cigarettes are generally smoked on a daily basis, the pulmonary consequences of marijuana smoking may be magnified by the greater deposition of smoke particulates in the lung due to the differing manner in which marijuana is smoked. Whereas THC causes modest short-term bronchodilation, regular marijuana smoking produces a number of long-term pulmonary consequences, including chronic cough and sputum, histopathologic evidence of widespread airway inflammation and injury and immunohistochemical evidence of dysregulated growth of respiratory epithelial cells, that may be precursors to lung cancer. The THC in marijuana could contribute to some of these injurious changes through its ability to augment oxidative stress, cause mitochondrial dysfunction, and inhibit apoptosis. On the other hand, physiologic, clinical or epidemiologic evidence that marijuana smoking may lead to chronic obstructive pulmonary disease or respiratory cancer is limited and inconsistent. Habitual use of marijuana is also associated with abnormalities in the structure and function of alveolar macrophages, including impairment in microbial phagocytosis and killing that is associated with defective production of immunostimulatory cytokines and nitric oxide, thereby potentially predisposing to pulmonary infection. In view of the growing interest in medicinal marijuana, further epidemiologic studies are needed to clarify the true risks of regular marijuana smoking on respiratory health.